Optimization of Biodiesel Yield Synthesized by Calcium Oxide Nano-catalyst Trans-esterified Jatropha curcas Oil - O. Eyide; W. C. Ulakpa; P. I. Nwabuokei (Journal of Applied Sciences and Environmental Management)
Biodiesel is a sustainable and environmentally friendly alternative fuel that is made with the use of a catalyst to increase yield under ideal operating circumstances. Concerns about pollution and energy supply can be effectively addressed by using this renewable energy source. Hence, the objective of this paper was to optimize biodiesel yield synthesized by calcium oxide (CaO) nano-catalyst trans-esterified Jatropha curcas oil (JCO) using Response Surface Methodology (RSM) through central composite design. These runs evaluated four process variables: the methanol-to-oil molar ratio (from 1:4 to 12:1), catalyst concentration (from 0.5 to 2.5 wt. %), reaction temperature (from 35 to 75 °C), and reaction time (from 40 to 80 minutes). With an 8:1 methanol-to-oil molar ratio, 1.5 wt.% catalyst concentration, 55 °C reaction temperature, and 60 minutes reaction time, the findings showed a peak biodiesel production of 96.51%. An R² of 0.9626, R² adj value of 0.9277, and predicted R² of 0.8505 were all output by the RSM quadratic model. As an added bonus, the biodiesel's primary physicochemical properties are in line with those of EN 14214 and ASTM D6751.